Constraining Elko dark matter at the LHC with monophoton events. (4th April 2018) - Alves, Alexandre; Dias, M.; de Campos, F.; Duarte, L.; Hoff da Silva, J. M.
Abstract: A mass-dimension-one fermion, also known as Elko, constitutes a dark-matter candidate which might interact with photons at the tree level in a specific fashion. In this work, we investigate the constraints imposed by unitarity and LHC data on this type of interactions using the search for new physics in monophoton events. We found that Elkos which can explain the dark matter relic abundance mainly through electromagnetic interactions are excluded at the 95% CL by the 8 TeV LHC data for masses up to 1 TeV.